2018
DOI: 10.3390/su10051348
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of the Role of China and India in Sustainable Textile Competition in the U.S. Market under Green Trade Barriers

Abstract: The United States is the most important textile import market in the world, and one of the most important export targets of developing countries. In view of its ecological environment and consumer health, the United States has put forward increasingly harsh environmental protection systems and standards for imported textile products, and its environmental trade barriers have been steadily strengthened. China's textile exports increased substantially after joining the World Trade Organization (WTO) in 2000; at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Several pieces of the literature have been reported on the study of sustainable competition. Xu et al revealed the characteristics of China and India's sustainable advantages and clarified that China and India have different impacts on the imports of related fields in the United States [3]. Zeng et al proposed that the role of information systems was played in developing countries and sustainable information infrastructure [4].…”
Section: Introductionmentioning
confidence: 99%
“…Several pieces of the literature have been reported on the study of sustainable competition. Xu et al revealed the characteristics of China and India's sustainable advantages and clarified that China and India have different impacts on the imports of related fields in the United States [3]. Zeng et al proposed that the role of information systems was played in developing countries and sustainable information infrastructure [4].…”
Section: Introductionmentioning
confidence: 99%
“…These indices are frequently used in studies for the textile sector [24,25,26,27], where global competition is increasing. It was used to examine the competition of the textile sectors in China [28,29], India [28,30,31], Pakistan [32] and the USA [20,29], which are important players. According to the results of these studies, China, Bangladesh, Vietnam, India and Türkiye are competitive countries in the textile sector.…”
Section: Many Methods Have Been Developedmentioning
confidence: 99%
“…Furthermore, China produces approximately 31% of the global ratio of synthetic fibers required by the modern textile industry [23] and produces nearly 65% of the world's clothing [24]. When China started imposing strict environmental standards on textile production, China's cloth products became more competitive in the United States (US) market [25].…”
Section: Textile Waste Generation and Management In Leading Economiesmentioning
confidence: 99%